2006
DOI: 10.1002/ijc.22453
|View full text |Cite
|
Sign up to set email alerts
|

The association of use of sunbeds with cutaneous malignant melanoma and other skin cancers: A systematic review

Abstract: Exposure to solar ultraviolet (UV) radiation is a known cause of skin cancer. Sunbed use represents an increasingly frequent source of artificial UV exposure in light‐skinned populations. To assess the available evidence of the association between sunbed use and cutaneous malignant melanoma (melanoma) and other skin cancers, a systematic review of the literature till March 2006 on epidemiological and biological studies on sunbed use was performed in Pubmed, ISI Web of Science, Embase, Pascal, Cochrane library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(94 citation statements)
references
References 88 publications
(213 reference statements)
1
93
0
Order By: Relevance
“…Sun protection in children has been demonstrated to reduce nevus formation (100). The link between sun exposure in early life and nevus and melanoma risk has led to increased legislation to restrict access to tanning beds for minors, the use of which has been associated with melanoma risk (101). …”
Section: Melanocytic Neoplasms Originating From Epithelial Melanocytesmentioning
confidence: 99%
“…Sun protection in children has been demonstrated to reduce nevus formation (100). The link between sun exposure in early life and nevus and melanoma risk has led to increased legislation to restrict access to tanning beds for minors, the use of which has been associated with melanoma risk (101). …”
Section: Melanocytic Neoplasms Originating From Epithelial Melanocytesmentioning
confidence: 99%
“…Long-term follow-up of psoriasis patients has demonstrated that those receiving UV-A therapy are at increased risk of developing melanoma [27]. Sunbeds emit UV-A radiation; a meta-analysis of studies [28] exploring melanoma incidence following sunbed use reported a 75% increase in risk in individuals under 35 with a history of sunbed use. Further studies support this finding, drawing clear associations between melanoma risk and the amount of sunbed usage, particularly from a young age [29–31].…”
Section: Cutaneous Melanomamentioning
confidence: 99%
“…In humans, UVA1 exposure during phototherapy sessions leads to acute side effects including skin dryness, pruritus, polymorphic light eruptions and herpes simplex virus reactivation [10], [11]. A potential carcinogenic effect in humans can be strongly suspected since these wavelengths are able to induce DNA lesions and mutagenesis, and an increasing risk towards melanoma has also been associated with use of sunbeds [5], [12], [13]. In addition, UVA1 wavelength range, in contrast to UVA2, is highly immunosuppressive in human in vivo and is thought to be the largest contributor to immunosuppression resulting from incidental daily sun exposure [14], [15].…”
Section: Introductionmentioning
confidence: 99%